PENGARUH FINANCIAL LITERACY, FINANCIAL INCLUSION DAN FINANCIAL TECHNOLOGY TERHADAP PERILAKU KEUANGAN PADA GENERASI Z - Nurul Fauziyah; Fatichatur Rachmaniyah; Siti Shoimah; S. Syaiful Rosyid (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the influence of financial literacy, financial inclusion, and financial technology on the financial behavior of Generation Z in Lamongan Regency. A quantitative approach was employed using a survey method involving 96 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using instrument testing, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) with SPSS version 25. The findings indicate that financial literacy and financial inclusion have a positive and significant effect on the financial behavior of Generation Z, while financial technology shows no significant effect. Simultaneously, financial literacy, financial inclusion, and financial technology collectively have a positive and significant impact on financial behavior, with an adjusted R² value of 0.578. These results highlight that financial knowledge and access to financial services play essential roles in shaping the financial behavior of young individuals in the digital era, whereas financial technology alone is insufficient to influence behavior without adequate literacy.